A causal analysis of developmental assets, behaviors and delinquency among hispanic youth in Texas - Nascimento de Carvalho, Jackson (2007)
According to the uniform crime report (2003), about 2.3 million youth under the age of eighteen area arrested every year in the United states, and many more cases go unreported